Contemporary art and networks: Analysis of the Venus Project using the UCINET software - Benito, Patricia V. (AWARI, 2022)
During the first years of the 21st century, the political, economic, and institutional crisis in Argentina, linked to the fall of the convertibility plan; led to the strengthening of associative, collaborative, and community livelihoods (Hintze, 2003; Palomino, 2005; Pastore, 2010). In dialogue with this situation, from the field of visual arts, the Venus Project arises, a network of artists created in Buenos Aires, Argentina. Venus, operated from 2002 to 2006, offers a virtual and analog platform for exchanging services, goods, skills, and/or knowledge between artists and agents interested in cultural consumption and its management. The project aimed to create a micro-community with an experimental authartic economy and its own currency (Pauls, 2002; Sainz and Solaas, 2007; Krochmalny, 2008; Rubinich, 2009; Jacoby, 2011). Throughout its five years, the network had more than 600 members linked through offers and demands. In the present work, the reconstruction of the total network of experience is proposed to identify the flow of exchanges and analyze their effectiveness. Our hypothesis is that it failed to function as an economic device, framed within a collective artistic proposal. In turn, for the survey of our corpus, we use techniques that come from ethnography, data that will be analyzed later from the UCINET software.